The big, big wall - Howard, Reginald; Dewey, Ariane; Aruego, Jose (San Diego : Harcourt, 2000)
Humpty Dumpty's friends help him avoid a big, big fall.
Keywords: Stories in rhyme; Characters in literature; Eggs; Friendship